2022
DOI: 10.1080/15623599.2022.2040076
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and strategies for building information modelling implementation: a comparative study between New Zealand and China

Abstract: Building Information Modelling (BIM) is a sharing platform that can present a parametric 3D model with various project information in the form of a digital display. In recent years, BIM adoption has become increasing globally as the Architectural, Engineering, Construction (AEC) industry has recognised its benefits. Meanwhile, many challenges of BIM adoption in different countries have been well documented. To address the gap in literature, this study examines the differences and similarities of BIM adoption b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…'High cost of software purchase/licensing' is considered the most critical barrier by designers and builders. This finding substantiates findings of previous studies which have identified the costs of software to leverage the full benefits of digitalisation of construction (Love and Irani, 2001, Olatunji and Construction, 2011, Ma et al, 2022. This is followed 'High cost of digital tools and setting up equipment'.…”
Section: Barriers To Improving the Status Of Digitalisation In Design...supporting
confidence: 90%
See 1 more Smart Citation
“…'High cost of software purchase/licensing' is considered the most critical barrier by designers and builders. This finding substantiates findings of previous studies which have identified the costs of software to leverage the full benefits of digitalisation of construction (Love and Irani, 2001, Olatunji and Construction, 2011, Ma et al, 2022. This is followed 'High cost of digital tools and setting up equipment'.…”
Section: Barriers To Improving the Status Of Digitalisation In Design...supporting
confidence: 90%
“…Several researchers have explored drivers and barriers to digitalization of construction predominantly in terms of the adoption of a few prominent technologies. Ma et al (2022) explored barriers to implementing Building Information Modelling (BIM) by consultants and contractors in New Zealand and China with a cross-analysis between the two countries. Further studies included identifying a refined set of drivers and barriers to BIM uptake in the UK, focusing on architectural practices (Jones, 2020) and the adoption of virtual reality by UK construction consultants (Badamasi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of the transfer of knowledge, individuals' confidence and ability to use BIM inspires them to share the knowledge of BIM they had received through training. This assertion supports Ma et al (2022), Pikas et al (2013) and Son et al (2014) about gaining confidence through knowing BIM and learning BIM. This study concludes that the above knowledge sharing leads to more frequent and intensive use of BIM training skills rather than the notion that computer self-efficacy directly influences BIM usage.…”
Section: Conclusion Implications and Future Researchsupporting
confidence: 68%
“…The general BIM adoption in QS practices in Hong Kong is consistent with previous BIM studies. In a number of BIM research studies, quality models and QS information requirements have also been endorsed as being imperative to support an efficient 5D BIM process (Aragó et al, 2021;L. Ma et al, 2022;Olatunji et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Ma et al (2020) discovered that lack of technical personnel, lack of knowledge and experience for BIM implementation, and missing regulations and rules are among the most critical barriers to BIM implementation in China. Ma et al (2022) suggested that knowledge barrier is one of the most critical barriers in New Zealand. The similar barriers have been discovered in Australia as well (Olatunji et al, 2021).…”
Section: Challenges Of Bim Adoption In Qs Practicesmentioning
confidence: 99%